MODEL PERSAMAAN STRUKTURAL DENGAN ESTIMASI METODE KUADRAT TERKECIL - , SURANTO,S.Pd ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Regression analysiscan not simultaneously analyze the relationship between several latent variables. Structural equation modeling was developed to overcome this problem. This model consists oftwo models, namely the structural model and the measurement model. This Research studies structural equation modeling stage least squares methodof the model specification, charting path diagram, identification, estimation and test the suitability of the model to the data. From modeling proposed in this study in the form of case studies of climate and motivation contribute to the performance of teachers in MTsN Boyolali, obtained results that the model supported by the data. Where the work climate affects work motivation with 17.18 statistic value above the critical value of 1.96. Work climate affects teacher performance with 10.95 statistical value above the critical value 1.96. Work motivation affects teacher performance with 7.62 statistic value abovethe critical value of1.96.